Nomenclatural Acts: homonymy in the Ascidiacea (Tunicata) and proposed nomina nova - Brunetti, Riccardo (Zootaxa, 2007)
In a revision of 4356 species and sub species of the class Ascidiacea, 15 were found to be homonyms for which nomina nova are proposed in this paper. The paper refers only to the nomenclature of these entities; and their taxonomy is not discussed here.